State of knowledge of the Theory of Semiotic Representation Records in annals of the National Day of Mathematical Education – JEM (Research, Society and Development, 2021)
Scientific events are essential for the dissemination of knowledge generated by science, it is through them that communication between scientists takes place and it is possible to observe the development of each field of research. Therefore, this work aims to present an overview of the researches that approach Raymond Duval's theory of semiotic representation records and the mathematical object function. The mapped surveys are from the National Day of Mathematical Education - JEM, an event held at the University of Passo Fundo, in Rio Grande do Sul. It is a biennial event, the first edition of which was held in 2006 and is currently in its eighth edition, carried out in 2020 and which occurred remotely due to the COVID-19 pandemic. This research has a qualitative approach and the mapping is of the State of Knowledge type. It is noteworthy that the content of function was considered due to being one of the most important concepts in Mathematics, its idea is present in everyday life, in addition to having great applicability in other areas of knowledge. It was possible to find 19 works referring to Duval's theory, but only 7 made reference to the function and are distributed in the II JEM, III JEM, V JEM and VII JEM. It was noticed that the second edition is the one with the most results, with a total of 3. The cataloged searches belong to the federative unit of Rio Grande do Sul, it is expected that in the next editions there will be more participation from other states and regions.